(untitled) (The Research of Medical Science Review, 2024)
Vernal keratoconjunctivitis (VKC) is inflammation of the cornea seen usually in young children and adolescents, which often aggravates during summer and peaks in spring. Mast cell stabilizers are widely used long-term without any significant side effects. For patients who do not respond to mast cell stabilizers, the treatment has to be potentiated by another agent such as steroids like fluorometholone. Given the propensity of patients in Pakistan to self-medicate, the unsupervised and self-prescribed use of steroids is a real risk leading to hazards such as raised IOP, especially after long-term use. A safe long-term steroid alternative to supplement sodium cromoglycate thus assumes significant importance. This is why tacrolimus has been selected as a steroid-sparing agent in this study, The quantitative observational study was conducted in the Department of Paediatric Ophthalmology, Children's Hospital and Institute of Child Health, Children Hospital Lahore. The 4-week study included 60 male and female patients of primary VKC between 6 to 16 years of age. Using systemic random sampling the patients were divided into Group 1 (n=30), which was treated by using 4% sodium cromoglycate eye drops only, while in Group 2 (n=30), 0.03% tacrolimus eye ointment was also added. Pre- and post-treatment signs and symptoms of the patients were recorded and their difference was denoted as the Relief Score, The mean Relief Scores of Group 2 (n=30) were found to be significantly higher than those of Group 1 (n=30), with a p-value of less than 0.05. A combination of sodium cromoglycate with tacrolimus eye ointment was found to be more effective than sodium cromoglycate alone, Higher efficacy was observed in treating vernal keratoconjunctivitis when 0.03% tacrolimus eye ointment was added to 4% sodium cromoglycate eye drops. This makes tacrolimus a viable steroid-sparing agent, especially in prolonged or particularly resistant cases where steroid side effects are particularly troublesome.